2013
DOI: 10.1007/s11552-013-9517-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Movement Phases of the Hand during Lateral and Pulp Pinches Using Video Motion Capture

Abstract: VMC is a feasible and valid method for objectively quantifying dynamic movement of multiple joints simultaneously. The results provide new insight to the dynamics of hand movement as well as a basis for subsequent evaluations of movement patterns performed in ADLs and instrumental ADLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The implants were loaded axially and at 30°, the latter representing the maximum excursion of the CMC joint from the neutral position (Kapandji, 1986). A motion capture study of thumb pinch (key pinch and tip pinch) showed that the CMC joint moves about half of this angle (12.9° for key pinch and 16° for tip inch) during the two types of pinch which are the situations where the thumb is maximally loaded in daily life (Jahn et al, 2013). Thus, one could argue that we should have used a smaller angle, but we do not think the exact angle is of great importance in this study.…”
Section: Discussionmentioning
confidence: 90%
“…The implants were loaded axially and at 30°, the latter representing the maximum excursion of the CMC joint from the neutral position (Kapandji, 1986). A motion capture study of thumb pinch (key pinch and tip pinch) showed that the CMC joint moves about half of this angle (12.9° for key pinch and 16° for tip inch) during the two types of pinch which are the situations where the thumb is maximally loaded in daily life (Jahn et al, 2013). Thus, one could argue that we should have used a smaller angle, but we do not think the exact angle is of great importance in this study.…”
Section: Discussionmentioning
confidence: 90%
“…We recognize that our unidirectional testing at a constant load of 50 N represents a simplification of the clinical situation where the load will vary in direction and magnitude. For many daily activities the load passing through the thumb will be low and higher loads will generally pass through a stabilized joint with little or no motion occurring during various forms of lateral or pulp pinch, as confirmed by Jahn et al in their video motion capture study (Jahn et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
“…Jahn et al 29 conducted an investigative study on hand movements during pinch activities via motion capture technique. Four right dominant volunteers (one female and three males) of Mean ± SD Age: 27.5 ± 2.5 years participated in the study.…”
Section: Resultsmentioning
confidence: 99%